Associations of COVID-19 vaccination during pregnancy with adverse neonatal and maternal outcomes: A systematic review and meta-analysis - Cailin Ding; Yakun Liu; Wenbo Pang; Dan Zhang; Kai Wang; Yajun Chen (Frontiers Media S.A., 2023)
ObjectivesThe low COVID-19 vaccine uptake rate among pregnant women is mainly due to safety concerns about COVID-19 vaccines due to limited safety evidence. Our goal was to evaluate the safety of COVID-19 vaccination during pregnancy with up-to-date evidence.MethodsA comprehensive search of MEDLINE, EMBASE, the Cochrane Library, and clinicaltrials.gov was performed on April 5th, 2022, and updated on May 25th, 2022. Studies evaluating the association of COVID-19 vaccination during pregnancy with adverse maternal and neonatal outcomes were included. Two reviewers independently performed the risk of bias assessment and data extraction. Inverse variance random effect meta-analyses were performed to pool outcome data.ResultsForty-three observational studies were included. COVID-19 vaccination [96,384 (73.9%) BNT162b2, 30,889 (23.7%) mRNA-1273, and 3,172 (2.4%) other types] during pregnancy [23,721 (18.3%) in the first trimester, 52,778 (40.5%) in the second trimester, and 53,886 (41.2%) in the third trimester].was associated with reduced risks of stillbirth or neonatal death (OR, 0.74; 95% CI, 0.60-0.92). Sensitivity analysis restricted to studies in participants without COVID-19 showed that the pooled effect was not robust. COVID-19 vaccination during pregnancy was not associated with congenital anomalies (OR, 0.83; 95% CI, 0.63-1.08), preterm birth (OR, 0.98; 95% CI, 0.90-1.06), NICU admission or hospitalization (OR, 0.94; 95% CI, 0.84-1.04), an Apgar score at 5 min <7 (OR, 0.93; 95% CI, 0.86-1.01), low birth weight (OR, 1.00; 95% CI, 0.88-1.14), miscarriage (OR, 0.99; 95% CI, 0.88-1.11), cesarean delivery (OR, 1.07; 95% CI, 0.96-1.19), or postpartum hemorrhage (OR, 0.91; 95% CI, 0.81-1.01).ConclusionsCOVID-19 vaccination during pregnancy was not associated with any of the adverse neonatal or maternal outcomes studied. Interpretation of study findings is limited by the types and timing of vaccination. The vaccinations in our study received during pregnancy were primarily mRNA vaccines administered in the second and third trimester. Future RCTs and meta-analysis are warranted to evaluate the efficacy and long-term effects of the COVID-19 vaccines.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42022322525, identifier: PROSPERO, CRD42022322525.